2016
DOI: 10.3390/beverages2040031
|View full text |Cite
|
Sign up to set email alerts
|

Tune That Beer! Listening for the Pitch of Beer

Abstract: We report two experiments designed to assess the key sensory drivers underlying people's association of a specific auditory pitch with Belgian beer. In particular, we assessed if people would rely mostly on the differences between beers in terms of their relative alcohol strength, or on the contrast between the most salient taste attributes of the different beers. In Experiment 1, the participants rated three bitter beers (differing in alcohol content), using a narrow range of pitch choices (50-500 Hz). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Crisinel and Spence [8] mapped the correspondence between basic taste and flavours with musical notes. Soundscapes were further reported to influence the basic taste of cinder toffee [9], beer [4,6], and ice cream [10,23]. The emotional mediation theory [13,23] was proposed to explain these crossmodal effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crisinel and Spence [8] mapped the correspondence between basic taste and flavours with musical notes. Soundscapes were further reported to influence the basic taste of cinder toffee [9], beer [4,6], and ice cream [10,23]. The emotional mediation theory [13,23] was proposed to explain these crossmodal effects.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, researchers have been exploring crossmodal correspondences between sounds and the taste, aroma, flavour and/or texture of foods. Studies investigating the effects of audition on other senses have examined the influence of auditory cues on odours such as roasted coffee [1]; potato-chips and coffee [2] and vanilla [3]; tastes such as bitter and sweet [3,4,5,6,7,8,9,10,11,12,13], and; textures such as crunchiness [14], crispness [15], and carbonation [16]. These findings have important implications as sound has the potential to be modulated to enhance the consumer’s eating experience by manipulating the emotional congruency between sound and food perception.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated that the higher alcohol content export lager tended to be matched with a higher pitch of pure tone, when a small number of participants (c. ten) were invited to select the "pitch of harmony" by varying the sound made by a tone generator. Although a subsequent follow-up only partially supported the claim that different food and beverage products are matched with different pitches of sound (Rudmin and Cappelli, 1983), Reinoso Carvalho et al (2016b) were able to demonstrate a robust cross-sensory mapping between beers and cola having different pitches. In 2020, Beck's launched a similar pitch-based experiential activation using music tracks mixed by Brazilian DJs, entitled "Beck's Frequency" (Fernández, 2020;Gianatasio, 2020b).…”
Section: Beermentioning
confidence: 89%
“…Early studies of sonic seasoning focused specifically on the matching of the frequency of a pure tone with food and beverage items presenting a specific flavour (e.g., Holt-Hansen, 1968 , 1976 ; Rudmin and Cappelli, 1983 ; and see Reinoso Carvalho et al, 2016b , for a more recent study adopting much the same approach). In the majority of contemporary cases of sonic seasoning, specially composed soundscapes and/or pre-recorded music selections have been designed to match, and hence to emphasize, a specific element in the multisensory tasting experience.…”
Section: Multisensory Flavour Perception and Sonic Seasoning: The Basicsmentioning
confidence: 99%
“…Different studies have also shown that certain pitch or auditory frequency ranges correspond with specific taste/flavor sensations, such as bitterness, sourness, and sweetness [ 17 , 18 , 19 , 20 ]. Based on these insights, music can be produced or selected in order to deliberately correspond to specific taste sensations [ 1 , 18 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%